(NrECIDIWIST(B: [(NrOMAN(B]; s (NkNIGA PERWAQ (B/ s (N~ASTX (B5s - (NwONNEGUT(B, (NkURTs ((NmOSKWA(B: s (NsTART(B, s, 1992)
(NdWA WNECIKLOWYH ROMANA(B.s
(NsINQQ BORODAs
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs; (NsOCIALXNYJ ROMANs -- (NfANTASTIKAs